PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP PURCHASE INTENTION RESERVASI HOTEL YANG DIMEDIASI OLEH VARIABEL BRAND IMAGE (STUDI PADA PENGGUNA SITUS TRAVEL ONLINE AIRY ROOMS) - Ratnandika, Yuvita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This research aims to determine and analyze the direct and indirect influence of electronic word of mouth on hotel reservation intention mediated by brand image as the intervening variable. This explanatory research explains the causal relationship between variables through hypothesis testing. This study uses a sample of 100 individual respondents who have read online hotel review in Airy Rooms at least once. The hypothesis testing was done using T test and Sobel test. The data were analyzed using Partial Least Squares (PLS), in Smart PLS 3.0. Based on the four hypotheses, it can be concluded that electronic word of mouth has a positive but insignificant influence on the intention of reserving hotel rooms in Airy Rooms’ website, that electronic word of mouth has a positive and significant effect on the brand image of hotels in Airy Room’ website, and that brand image has a positive and significant effect on customer’s intention to reserve hotel rooms in Airy Rooms’ website. Furthermore, electronic word of mouth has a positive and significant influence on consumer’s intention to reserve hotel rooms in Airy Rooms’ s website with completemediation of brand image. KEYWORDS: Electronic Word of Mouth (E-WOM), Brand Image, Purchase Intention